Growing resilient futures: agroforestry as a pathway towards climate resilient development for smallholder farmers - Taillandier, Chloé; Cörvers, Ron; Stringer, Lindsay C. (Frontiers in Sustainable Food Systems, 2023)
Climate change is increasing pressure on communities that are already experiencing high levels of vulnerability and poverty, threatening their subsistence. Among the most vulnerable are smallholder farmers in the Global South, who rely on their yields for food and income. Smallholders need to adapt to changes in rainfall, temperature, and weather patterns and their knock-on effects, and at the same time, ensure that their on-farm climate adaptations do not make climate change worse by increasing greenhouse gas emissions. The Intergovernmental Panel on Climate Change (IPCC) emphasises the need for Climate Resilient Development Pathways (CRDPs) to support vulnerable communities, including smallholder farmers, in balancing climate adaptation, mitigation and development. CRDPs comprise reactive and/or preventive actions that key stakeholders (e.g. government, business, civil society and individuals, including smallholder farmers) can take to become more resilient in the context of a changing climate whilst not compromising their development or increasing emissions. The CRDP framework has so far remained conceptual, providing little information on how to actually create these pathways in practice. This paper addresses this gap, and with a focus on agroforestry projects and smallholders in the Global South, assesses how CRDPs can become more concrete and actionable through a focus on agroforestry: the voluntary combination of crop and/or pasture with trees and/or shrubs, considering its contribution to climate adaptation, mitigation and development.We draw on literature review and focus group data, analysed using Atlas.ti 23 and a coding process to present a tool relevant to project designers, policymakers and researchers to assess agroforestry projects according to different aspects of climate resilient development, with particular focus on smallholder farmers in the Global South.Evaluation of the tool found it is relevant and useful for project developers and funders to check that their projects follow the components of CRD, but the tool needs to be translated to the local context to better address local demands and reflect regional specificities, which focus group participants deemed possible.